2021
DOI: 10.1111/jam.15162
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis WLYS23 strain possesses antagonistic activity against hybrid snakehead bacterial pathogens

Abstract: Aim:The aims of this study were to screen an antagonistic probiotic for the prevention and control of bacterial diseases in snakehead fish and to evaluate the antimicrobial activities, biosafety and biocontrol effect of the antagonistic strain. Methods and Results: In this study, the WLYS23 strain exhibiting the most effective antagonistic properties against several fish pathogens was selected from the intestine of healthy snakehead fish. The strain was identified as Bacillus velezensis based on morphological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…Strain B. velezensis SZMC 24986 showed promising in vitro antagonism against all of the tested strains of fungal species known as plant pathogens. The antibacterial and antifungal effects of this species were described earlier [54][55][56], which supports this strain as a potential candidate for biocontrol purposes. Nitrogen-fixing bacteria play an important role in the soil, therefore they are becoming important parts of multicomponent soil inoculants [57].…”
Section: Discussionsupporting
confidence: 63%
“…Strain B. velezensis SZMC 24986 showed promising in vitro antagonism against all of the tested strains of fungal species known as plant pathogens. The antibacterial and antifungal effects of this species were described earlier [54][55][56], which supports this strain as a potential candidate for biocontrol purposes. Nitrogen-fixing bacteria play an important role in the soil, therefore they are becoming important parts of multicomponent soil inoculants [57].…”
Section: Discussionsupporting
confidence: 63%
“…The characterizations of LB-Y-1 were done using the method explained by Zhang D. F. et al (2021) with minor modifications. The characteristic colonies were gram stained, and bacteria were examined for morphology under a light microscope (Olympus CX40, Olympus Optical Co. Ltd., Hamburg, Germany) and a scanning electron microscopic (SEM, Inspect F50, FEI Company, Hillsboro, OR, United States; Bajpai et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…In order to further examine the potential of LB-Y-1 to produce multi-enzymes, the activity of amylase and lipase in the LB-Y-1 were determined using the solid agar plate method ( Zhang D. F. et al, 2021 ). Briefly, after cultured in LB broth at 37°C overnight, the strain was stab-inoculated on the surface of LB agar plate containing 1.5% soluble starch or 1% triglyceride tributyrate (four replicates were made of each assay).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, the risk of fish disease has increased. Studies have shown that viruses, bacteria, fungi and parasites are the main causes of fish diseases, with bacterial diseases accounting for the highest proportion and causing the greatest losses (Garrido‐Olvera et al, 2022; Kibenge, 2019; Scholz et al, 2021; Zhang, Han, et al, 2021; Zhang, Xiong, et al, 2021). Aeromonas hydrophila is one of the pathogenic bacteria in fish, which can not only cause septicaemia in fish, but also pose a threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of fish probiotics has attracted the interest of many researchers, because these probiotics can not only inhibit the growth of fish pathogenic bacteria, but also without pollution to the environment. Zhang, Han, et al (2021); Zhang, Xiong, et al (2021) showed that Bacillus velezensis WLYS23 screened in the gut of hybrid snakehead has antagonism to 20 species of fish pathogens such as Aeromonas hydrophila , Aeromonas veronii , Aeromonas aquariorum , Aeromonas shigelloides and Nocardia seriolae . Streptomyces amritsarensis N1‐32 screened from soil by Li and Chen (2019) has an antagonistic effect on 10 fish pathogens such as Aeromonas hydrophila , Aeromonas veronii , Aeromonas caviae .…”
Section: Introductionmentioning
confidence: 99%